2020
DOI: 10.1155/2020/8196014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Paraben Concentration and Its Association with Serum Triglyceride Concentration in 2013-2014 NHANES Participants: A Cross-Sectional Study

Abstract: Background. Alkyl esters of para-hydroxybenzoic acid, colloquially known as parabens, are types of preservatives found in multiple foodstuffs, pharmaceuticals, and personal care products to which Americans are exposed daily. It is unclear if parabens exhibit endocrine-disrupting properties. Parabens may interact with triglycerides in adipose tissue and impact lipid metabolism. Objective. To evaluate the association between urinary paraben concentrations and serum triglyceride concentrations. Design. A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Studies have shown a link between MeP and PrP excretion in urine and reduced levels of circulating triglycerides. 21 Recent molecular studies have provided further insight into this phenomenon. For instance, a study with zebrafish reported down-regulation of transcription factors involved in lipid homeostasis, including triglycerides, in the livers of female fish exposed to MeP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a link between MeP and PrP excretion in urine and reduced levels of circulating triglycerides. 21 Recent molecular studies have provided further insight into this phenomenon. For instance, a study with zebrafish reported down-regulation of transcription factors involved in lipid homeostasis, including triglycerides, in the livers of female fish exposed to MeP.…”
Section: Discussionmentioning
confidence: 99%
“…The following concentrations were used for PP, MP, and BP: 0.002 µM, 0.02 µM, 0.2 µM, 2 µM, and 20 µM. These concentrations fall within the range of what has been measured in biological samples in the NHANES biomonitoring study [14][15][16][17][18][19][20] and in breast tissue [21,22,[26][27][28][29]39]. Treatments were done in triplicates, and experiments were repeated six times.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Hormonally hazardous chemicals have been linked to breast cancer; specifically, studies have found estrogenic properties in paraben-laden hair and other personal care products that are heavily marketed to Black women [11][12][13]. Parabens have been measured in biological samples from the NHANES biomonitoring study; across studies, the median/mean of PP levels are 4-15 g/L [14][15][16][17][18][19][20], the range of BP levels are 0.2-1,240 g/L [15,20], and the mean of MP levels are 38-63 g/L [15,17,[20][21][22]. There are racial/ethnic disparities in exposure to parabens.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollutants include the role of endocrine-disrupting chemicals (EDCs) (such as phthalates, parabens, triclosan, triclocarban, and diphenols) in the development of chronic diseases. EDCs contain many chemicals used in industry, commerce, agriculture, and pharmacy that have entered the water, air, food, human life, and wildlife [16][17][18]. ey can disrupt the function of the endocrine system and thus be harmful to human health [1,2,12,19].…”
Section: Introductionmentioning
confidence: 99%